(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article presents a literary analysis of Herman Melville’s Moby-Dick, focusing on its structural complexity, philosophical depth, and symbolic richness. By combining narrative theory and thematic exploration, the study reveals how Melville transforms a maritime adventure into a profound inquiry into human existence, identity, and the sublime. The findings emphasize Melville’s innovative approach to genre, narrative voice, and allegory.